Peran Pengawasan Keuangan Publik dalam Mewujudkan Transparansi Pengelolaan APBD di Kabupaten Sidoarjo - Muhammad Aufa Hafizh; Erika Rahma Novitasari; Revienda Anita Fitrie; Eva Hany Fanida (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of public financial oversight in Sidoarjo Regency, particularly the internal and external oversight mechanisms in the management of the Regional Revenue and Expenditure Budget (APBD). This study uses a qualitative descriptive approach with a literature study method sourced from scientific journals, government documents, and laws and regulations related to regional financial management. The results show that financial oversight in Sidoarjo Regency is implemented through two main mechanisms: internal oversight by the Regional Inspectorate as the Government Internal Supervisory Apparatus (APIP) and external oversight by the Supreme Audit Agency (BPK). Both mechanisms are implemented through audits, evaluations, monitoring, and examinations of regional government financial reports. In addition, the implementation of a regional financial information system plays a role in increasing transparency and accountability in budget management. These findings indicate that the synergy between internal and external oversight, supported by the digitalization of the financial system, contributes to increasing the effectiveness of APBD management in the region. The implications of this study emphasize that strengthening an integrated oversight system is necessary to realize more transparent, accountable, and efficient regional financial governance in supporting good governance in Sidoarjo Regency.